2016
DOI: 10.1177/1471301214558308
|View full text |Cite
|
Sign up to set email alerts
|

The experience of family carers of people with dementia who are hospitalised

Abstract: Hospital admission of a person with dementia can have a significant impact on the family carer, who temporarily relinquishes caring to health professionals. A descriptive qualitative design using in-depth interviews with a conversational approach was used to elicit data. Adjusting to the change in the carer's role can be challenging and result in feelings of helplessness, loneliness, loss of control and being undervalued. Family support can assist with the transition but family conflict increases anxiety. Good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 17 publications
2
70
0
Order By: Relevance
“…Our review found that family carers had limited confidence in their ability to manage the older person with dementia at home posthospital discharge. This may be in relation to studies suggesting that family carers are intimidated by the expert knowledge of health professionals (Bloomer et al, 2014;Emmett et al, 2014;Lindhardt et al, 2008). However, while clinicians may have expert knowledge, this is not readily translated to meaningful information to prepare the person for discharge.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Our review found that family carers had limited confidence in their ability to manage the older person with dementia at home posthospital discharge. This may be in relation to studies suggesting that family carers are intimidated by the expert knowledge of health professionals (Bloomer et al, 2014;Emmett et al, 2014;Lindhardt et al, 2008). However, while clinicians may have expert knowledge, this is not readily translated to meaningful information to prepare the person for discharge.…”
Section: Discussionmentioning
confidence: 93%
“…Family carer participation was often limited by lack of confidence. Most family carers want to be acknowledged as a resource to benefit care delivery, but were intimidated by the decision‐making process and the “expert” knowledge exhibited by health professionals (Bloomer et al., ; Emmett et al., ; Lindhardt et al., ; Mockford, ). Three studies highlighted that health professionals lack the skills and/or time to effectively engage with family carers of older people with dementia and therefore families’ knowledge of the person's health and social circumstances was not used (Emmett et al., ; Jurgens et al., ; Mortenson & Bishop, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carer dissatisfaction about the care provided to people with dementia in hospital relates to perceived poor care, lack of understanding of the needs of the person with dementia, deterioration in the health and function of the person with dementia, and limited involvement of and communication with carers . Care burden and exhaustion can also be experienced by carers who stay and support the person with dementia when hospitalised …”
Section: Introductionmentioning
confidence: 99%